SMEs' financial risks in supply chain trade with large companies: The case of Italian automotive component industry. (January 2022) - Errico, Marco; De Noni, Ivan; Teodori, Claudio
Becoming a supplier of large companies is traditionally considered to be positive for small and medium enterprises' (SMEs) competitiveness. Small businesses can take several advantages by joining supply chain trade with large companies such as scale efficiency and productivity as well as technological and managerial abilities, product and process innovation, market positioning, and reputation. However, not everything is convenient per se. The subcontracting by large companies might provide some financial criticalities that need to be faced and properly managed by SMEs to exploit supply chain benefits without affecting financial stability and losing competitiveness. In this direction, the literature on supply chain finance has recently focused on financial issues related to working capital optimization in terms of accounts payable, receivable, and inventories. Adopting this perspective, the study contributes to a better understanding of SMEs' financial constraints in supply chains driven by large companies by investigating a sample of small Italian firms, which operate in the metal casting industry and by comparing firms joining and not joining the automotive supply chain.